PEMBERDAYAAN MASYARAKAT MELALUI KAMPUNG PIA DI DESA KEJAPANAN KECAMATAN GEMPOL KABUPATEN PASURUAN - Mustofah, Reza Amalia; Sukmana, Hendra (Dinamika Governance: Jurnal Ilmu Administrasi Negara, 2025)
This study aims to describe and analyze the process of community empowerment through the Kampung Pia program in Kejapanan Village, Gempol District, Pasuruan Regency. The method used in this study is descriptive qualitative, with data collection techniques including observation, interviews, and documentation. The results of the study indicate that Community Empowerment through Kampung Pia in Kejapanan Village, Gempol District, Pasuruan Regency according to Mardi Yatmo Hutomo's (2000) Community Empowerment theory, namely (1) capital assistance in access to capital, the government has provided capital assistance, assistance provided by the government has an influence on business development, but assistance is not provided routinely and is limited to a number of recipients; (2) The development of facilities and infrastructure in its implementation still faces challenges, the pia center building which should be used as a marketing place cannot operate for long due to several obstacles, such as decreased sales due to the COVID-19 pandemic, unsupportive room temperatures, and problems with building permits that have not been completed; (3) mentoring, that the government previously provided mentoring such as training, now it is rare, the UMKM actors obtain information and training independently; (4) institutional strengthening, the Wasuka cooperative as the main institution of Kampung Pia has carried out institutional strengthening in the form of partnerships, participating in events, routine monthly cooperative meetings and submitting sponsors which aim to increase the capacity of the cooperative in supporting the development of UMKM Pia in Kejapanan Gempol Village. Keyword: Community Empowerment; Village Program; UMKM ABSTRAKPenelitian ini bertujuan untuk mendeskripsikan dan menganalisis proses pemberdayaan masyarakat melalui program Kampung Pia di Desa Kejapanan, Kecamatan Gempol, Kabupaten Pasuruan. Metode yang digunakan penelitian ini adalah deskriptif kualitatif, dengan teknik pengumpulan data meliputi observasi, wawancara, dan dokumentasi. Hasil penelitian menunjukkan bahwa Pemberdayaan Mayarakat melalui Kampung Pia di Desa Kejapanan Kecamatan Gempol Kabupaten Pasuruan menurut teori Pemberdayaan Masyarakat Mardi Yatmo Hutomo (2000) yaitu (1)bantuan permodalan dalam akses permodalan pemerintah sudah memberikan bantuan modal, bantuan yang diberikan pemerintah memiliki pengaruh terhadap perkembangan usaha, namun bantuan tidak diberikan secara rutin dan terbatas pada sejumlah penerima saja; (2)Pembanguan sarana dan prasarana dalam pelaksanaannya masi menghadapi tantangan, gedung sentra pia yang harusnya digunakan sebagai tempat pemasaran tidak dapat beroperasi lama karena beberapa kendala, seperti penurunan penjualan akibat pandemi COVID-19, suhu ruangan yang tidak mendukung, dan masalah izin mendirikan bangunan yang belum selesai; (3)pendampingan, bahwa pemerintah sebelumnya sudah memberikan pendampingan seperti pelatihan sekarang jarang adanya, para pelaku umkm memperoleh informasi dan pelatihan secara mandiri; (4)penguatan kelembagaan, koperasi wasuka sebagai lembaga utama Kampung Pia sudah melakukan penguatan kelembagaan dalam bentuk  kemitraan, mengikuti event, pertemuan rutin koperasi setiap bulan dan mengajukan sponsor yang bertujuan untuk meningkatkan kapasitas koperasi dalam mendukung pengembangan UMKM pia di Desa Kejapanan Gempol. Kata Kunci: Pemberdayaan Masyarakat; Program Kampung; UMKM